Women in prison in Spain:: the implementation of Bangkok rules to the Spanish prison legislation - Cerezo Domínguez, Ana Isabel (European journal on criminal policy and research, 2017)
This paper aims to take a close look at the reality of female crime in Spain. On the one hand, we will focus on describing the current situation of women incarcerated in Spanish prisons, an especially vulnerable group given their peculiarities and needs. Through secondary sources, we describe the situation of discrimination against women in these prisons. On the other hand, the paper establishes whether the current Spanish prison legislation echoes all or some of the United Nations Rules for the Treatment of Women Prisoners and Non-custodial Measures of Freedom for Women Offenders (Bangkok Rules, 2010). To this end, a detailed analysis of both standards, national and international, is essential. As a general conclusion, although Spain has high standard prison regulations and modern facilities, female prisoners in Spanish prison are subject to discrimination. It is from such a perspective that this article proposes that the necessary changes and appropriate penitentiary policies to meet the specific needs of female prisoners are established.